Funcionamiento familiar en adolescentes en riesgo de suicidio con rasgos de personalidad límite: un estudio exploratorio - Sara Marco-Sánchez; María Mayoral-Aragón; Fátima Valencia-Agudo; Laura Roldán-Díaz; Ana Espliego- Felipe; Carlos Delgado-Lacosta; Gonzalo Hervás-Torres (Revista de Psicología Clínica con Niños y Adolescentes, 2020)
Family functioning in suicidal adolescents with borderline personality traits. High prevalence of suicide in adolescent population all over the world is considered a world challenge in mental health. Family environment has been pointed as an important factor involved in adolescents’ suicide risk, playing a role not only as a risk factor but also as protective. This study has its goal on understanding which factors of the family functioning, measured by the Social Environment in the Family Scale, are related to the total score of the Beck Suicide Ideation Scale in a sample of 37 adolescents with ages between 14 and 17 years old (M = 15.76; SD = 1.06) borderline personality traits. It was hypothesized that worse levels of family functioning will increase suicide risk in adolescents. Results showed that the risk of suicide was higher when the Relationships Scale total score (quality of communication and interaction in the family) was lower. After analyzing each subscale separately, it was demonstrated the specific relevance of Expressivity Subscale, referred to the level of free expression of feelings in the family, suggesting that the lower expressivity in the family, the higher suicide ideation showed by the adolescents, and Social-Recreative, referred to the social participation and leisure of the family, what means the more social participation, the less suicide ideation. These results are supported by other studies that show the relevance of modifying the family environment for reducing the suicidal risk among adolescents. The value of this data involves taking into account the families in the treatment programs for suicidal adolescents.